Aetiology of obstructive azoospermia in Chinese infertility patients. (20th December 2015) - Han, H.; Liu, S.; Zhou, X.‐G.; Tian, L.; Zhang, X.‐D.
Summary: To explore the aetiology of obstructive azoospermia (OA) in Chinese infertility patients, 133 OA patients was included in this study diagnosed and evaluated by one major specialist trained urological infertility. We retrospected the medical records to collect relative information. All of the patients had been underwent physical examination, ultrasound scan to the urogenital system, serum hormone tests, genetic tests and two separate semen analyses. The mean age of all 133 patients was 32.7 ± 6.8 years. A total of 266 reproductive tract units (two/patient) were classified into four categories: no causes (Idiopathic) for 74 units (27.8%), single cause for 173 units (65.0%), double causes for 17 units (6.4%) and triple causes for two units (0.8%). As to single cause of OA, there were four types: trauma for 0 unit (0%), infection for 125 units (47.0%), dysplasia for 11 units (4.1%) and surgeries for 37 units (13.9%). As to total cause of OA, there were five types: infection for 144 units (54.1%), orchitis for 51 units (19.2%), epididymitis for 54 units (20.3%), gonorrhoea for 28 units (10.5%) and inguinal hernia repair surgery for 18 units (6.8%). The most frequent cause of obstructive azoospermia was infection revealed in these Chinese infertility populations, followed by idiopathic reason.